Perceived Value And Destination Image : Systematic Literature Reviews - Haryeni . (CV. ITTC INDONESIA, 2026)
The aim of this paper is to identify and analyze some of the main references of perceived value and destination image. This research is a systematic literature study using the Science Direct web and Emerald from the knowledge-based science citation index web. Based on several phases of the systematic review method, this study found 17 main references from the Scopus rankings Q1 and Q2. This study also examines behavioral quotes based on H-index article. This study found that Tourism Management (based on the number of citations) is the most influential journal that examines perceived value and destination image. However, most of the articles are in the field of tourism and only a few have researched specifically in the field of halal tourism. Most of the previous research discussed the relationship between destination image and perceived value and only a few examined the relationship between perceived value and destination image. This review contributes by identifying research trends, dominant relationships, and future research opportunities concerning perceived value and destination image based on high-quality Scopus-indexed publications.